Badania nad jednostkami konsumpcyjnymi we Francji w latach 1950 - 1963 - Gaudot, Georges (Wydział Prawa i Administracji UAM, 1972)
This study is a part of econometric research into the thesis: longevity of durable consumer goods that was presented at the University of Dijon in 1965. The thesis has been worked out by help of Stone and Rowe's model applied to the data supplied by the French national accounting for the period 1950 - 1963; the date can be extrapolated up to 1970. The author has assorted coefficients expressing the number of consumption units (Ni) with population categories according to sex, age, civil status, relation to the head of household and type of household. Having lettered the whole population with Pi the author worked out the coefficients λi=Ni/Pi for the year i from 1950 to 1963 (Table No. 3).
A Study of Consumptions Units in France, in 1950 - 1963